Trade credit: Contract-level evidence contradicts current theories - Tore Ellingsen; Tor Jacobson; Erik von Schedvin (Sveriges Riksbank, 2016)
We study 52 million trade credit contracts, issued by 51 suppliers over 9 years to about 199,000 unique customers. The data contain information on contract size, due dates, actual time to payment, and firm characteristics. Our empirical analysis contradicts the conventional view that trade credit is an inferior source of funding. Specifically, while we replicate the usual finding that payables are negatively related to customers' financial strength, our disaggregated data reveal that improvements in customers' financial conditions are primarily associated with a reduced value of input purchases rather than smaller trade credit usage. In fact, customers' financial conditions are unrelated to agreed contract duration and only modestly affect overdue payments. Moreover, the customer's size and share of the supplier's sales both have a positive impact on the due date. Overall, the evidence indicates that customers prefer trade credit over other available sources of funding and thus calls for a new theory of short-term finance.
Keywords: G32; G33; 330; Trade credit; Credit contracts; Financing constraints